2014
DOI: 10.1016/j.jns.2014.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Arterial spin-labeling magnetic resonance imaging for diagnosis of late seizure after stroke

Abstract: ASL was able to reveal hyperperfusion and was of great diagnostic value in the peri-ictal phase of late seizure after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In epilepsy, the series of patients studied with ASL include mostly subjects with mesial temporal lobe epilepsy [7,8]. Overall, these studies show increased perfusion during the peri-ictal period [9][10][11][12] and decreased perfusion during the post-ictal period [9,11,13], and these findings are globally concordant with electrophysiological studies, PET and/or singlephoton emission computed tomography (SPECT). Only individual cases with neocortical epilepsy have been reported [9,11,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 69%
“…In epilepsy, the series of patients studied with ASL include mostly subjects with mesial temporal lobe epilepsy [7,8]. Overall, these studies show increased perfusion during the peri-ictal period [9][10][11][12] and decreased perfusion during the post-ictal period [9,11,13], and these findings are globally concordant with electrophysiological studies, PET and/or singlephoton emission computed tomography (SPECT). Only individual cases with neocortical epilepsy have been reported [9,11,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 69%
“…It is therefore necessary to be aware that at any time after stroke, any type and location of stroke may cause a non-convulsive late seizure. As we recently reported (18), the demonstration of increased cortical perfusion by arterial spin-labeling MRI, which does not require a contrast agent, might be helpful in the early diagnosis of late seizures in the emergency department.…”
Section: Discussionmentioning
confidence: 86%
“…Arterial spin labeling (ASL) is a completely non-invasive and repeatable perfusion magnetic resonance image that uses magnetically-labeled water in the blood as an endogenous tracer. Recent studies have demonstrated that combined use of a perfusion image with ASL and diffusion-weighted imaging (DWI) can provide valuable information on the circulatory and metabolic consequences associated with epilepsy during ictal [ [1] , [2] , [3] , [4] , [5] , [6] , [7] ] or periictal (or postictal) periods [ 2 , [8] , [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%